Doktrin Tritunggal Jürgen Moltmann Sebagai Model Berpolitik Orang Kristen di Indonesia - Saragih, Febri Ando Pratama; Lubis, Nerti (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2024)
This paper aims to analyse the doctrine of the Trinity developed by Jürgen Moltmann, one of the theologians who presented his theory of the Trinity and then linked it to human socio-political activities. Christians in Indonesia exist in the midst of a pluralistic world. So the task of bringing God's light and love in all aspects of life, including politics, in the midst of a plural world is very important to do. The writing of this article departs from the phenomenon of apathy shown by Christians in Indonesia towards politics, so that Christians are reluctant to focus their attention on political activities in Indonesia. This research uses a descriptive qualitative approach, with a literature study method, which examines and reviews the socio-political analogy of Jürgen Moltmann's Trinity doctrine as he explains in his book The Trinity and The Kingdom. The research found that the doctrine of the Trinity, which is considered difficult and complicated at the level of systematic theological discourse, has made a great contribution to the lives of believers, including politics. The doctrine of the Trinity developed by Jürgen Moltmann invites all believers to take part in an ideal socio-political life, thus producing a concrete model for the socio-political life of Christians in Indonesia.